Computational investigation of the effects of knee airbag design on the interaction with occupant lower extremity in frontal and oblique impacts. (17th February 2017) - Nie, Bingbing; Crandall, Jeff R.; Panzer, Matthew B.
ABSTRACT: Objective : The lower extremity of the occupant represents the most frequently injured body region in motor vehicle crashes. Knee airbags (KABs) have been implemented as a potential countermeasure to reduce lower extremity injuries. Despite the increasing prevalence of KABs in vehicles, the biomechanical interaction of the human lower extremity with the KAB has not been well characterized. This study uses computational models of the human body and KABs to explore how KAB design may influence the impact response of the occupant's lower extremities. Methods : The analysis was conducted using a 50th percentile male occupant human body model with deployed KABs in a simplified vehicle interior. The 2 common KAB design types, bottom-deploy KAB (BKAB) and rear-deploy KAB (RKAB), were both included. A state-of-the-art airbag modeling technique, the corpuscular particle method, was adopted to represent the deployment dynamics of the unfolding airbags. Validation of the environment model was performed based on previously reported test results. The kinematic responses of the occupant lower extremities were compared under both KAB designs, 2 seating configurations (in-position and out-of-position), and 3 loading conditions (static, frontal, and oblique impacts). A linear statistical model was used to assess factor significance considering the impact responses of the occupant lower extremities. Results : The presence of a KAB had a significant influence on the lower extremity kinematics compared to no KAB ( P <.05) by providing early restraint and distributing contact force on the legs during airbag deployment. For in-position occupants, the KAB generally tended to decrease tibia loadings. The RKAB led to greater lateral motion of the legs compared to the BKAB, resulting in higher lateral displacement at the knee joint and abduction angle change (51.2 ± 21.7 mm and 15° ± 6.0°) over the dynamic loading conditions. Change in the seating position led to a significant difference in occupant kinematic and kinetic parameters ( P <.05). For the out-of-position (forward-seated) occupant, the earlier contact between the lower extremity and the deploying KAB resulted in 28.4° ± 5.8° greater abduction, regardless of crash scenarios. Both KAB types reduced the axial force in the femur relative to no KAB. Overall, the out-of-position occupant sustained a raised axial force and bending moment of the tibia by 0.8 ± 0.2 kN and 21.1 ± 8.7 Nm regardless of restraint use. Conclusions : The current study provided a preliminary computational examination on KAB designs based on a limited set of configurations in an idealized vehicle interior. Results suggested that the BKAB tended to provide more coverage and less leg abduction compared to the RKAB in oblique impact and/or the selected out-of-position scenario. An out-of-position occupant was associated with larger abduction and lower extremity loads over all occupant configurations. Further investigations are recommended to obtain a full understanding of the KAB performance in a more realistic vehicle environment.